Identification of the connection between tourism demand and economic growth in ASEAN-3 - Satawat Wannapan (2018)
Copyright © 2018 Inderscience Enterprises Ltd. This paper is based on the Bayesian inference to explore two purposes. First, the specific objective is proposed to consider an empirical analysis employing the panel Bayesian vector autoregressive (PBVAR) model. Secondly, the empirical study is aimed to analyse the driven factor between tourism demands and service sectors by adapting Granger-causality Bayesian test. Technically, the simulated computation called Markov chain Monte Carlo (MCMC) approach is employed to investigate the research’s findings. Yearly time-series data of tourism growth (tourist arrivals) and economic growth (service sectors) in ASEAN-3 countries such as Singapore, Thailand, and Malaysia were observed during 1996–2015. The empirical results of this study will deeply clarify the linkage between tourism demands and economy in ASEAN-3 countries and give recommendations to more assure that a suitable tourism policy is appropriately activated.